Makna Jihād Dan Reorientasinya Di Era Kontemporer (Analisis Komparatif Penafsiran Quraish Shihab Dan Wahbah Zuhaili Terhadap Qs Al-Taubah [9]: 73) - Masruroh, Durrotul; Anas, Khoirul (Global Education Journal, 2023)
The author focuses this research on comparing the thoughts of Wahbah Zuhaili and M Quraish Shihab regarding the meaning of jihād in QS al-Taubah [9]: 73. Later in this study the author also reorients the meaning of jihād according to the current context. In this study, researchers used qualitative research that emphasizes library research to produce descriptive data and researchers also used a comparative method that compares the thoughts of Wahbah Zuhaili and M Quraish Shihab regarding the meaning of jihād in QS al-Taubah [9]: 73 with triangulation data collection techniques. The results of this study show that Quraish Shihab and Wahbah Zuhaili interpretations of al-Taubah [9]:73 both confirm that the verse commands the Prophet to be harsh on infidels and hypocrites, even if necessary, allowed to fight them with weapons. But what distinguishes the interpretation of the two is that Quraish Shihab, in interpreting QS al-Taubah [9]:73 gives leeway in his interpretation regarding the form or way of jihad, which is according to the conditions needed and the last option is jihad with weapons. While Wahbah Zuhaili has asserted that QS al-Taubah [9]:73 there is no word to indicate that jihad in that verse is jihad by the sword or by oral and other means.